A high-efficiency CO adsorbent and preparation method thereof
Through two-step thermal dispersion and porous crosslinked fiber spraying, the high energy consumption and pollution problems in the preparation process of traditional activated carbon-based carbon monoxide adsorbents are solved, and the stability and adsorption performance of the adsorbent are improved.
Patent Information
- Application Number
- CN202210045594.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-01-15
AI Technical Summary
The preparation process of traditional activated carbon-based carbon monoxide adsorbents requires high temperature heating, resulting in high energy consumption and ionic contamination of Cu(II) solution. At the same time, the copper salt on the surface of activated carbon loaded with Cu after forming is insufficient adhesion, which is easy to lose powder and affects the adsorption performance.
Cu(I) was introduced by a two-step thermal dispersion method. The second step of thermal dispersion was carried out simultaneously with the binder cross-linking reaction and Cu(II) reduction reaction, which reduced the molding temperature and heating time, and sprayed porous cross-linked fibers: sodium carboxymethylcellulose-sodium alginate on the surface of the activated carbon to improve surface adhesion.
It achieves higher energy utilization efficiency and shorter heat dispersion time, avoids the environmental pollution of Cu2+ and Cl-ions, and improves the stability and adsorption performance of adsorbents.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adsorbent synthesis, and in particular relates to an activated carbon-based CO adsorbent and a preparation method thereof. Background Art
[0002] As an important chemical raw material, carbon monoxide is widely used in chemical synthesis. At the same time, with the vigorous development of hydrogen fuel cells, the demand for hydrogen for fuel cells is gradually increasing, and the development of hydrogen purification related technologies has entered a rising period. At present, most of the raw gas for hydrogen purification comes from the by-product hydrogen of refineries. The carbon monoxide content is difficult to meet the standard and needs to be removed with the help of special carbon monoxide adsorbents. Traditional carbon monoxide adsorbents can be divided into activated carbon-based and molecular sieve-based. Cu (I) is introduced into the adsorbent structure, pores or surface through ion exchange, thermal dispersion or impregnation. With the help of π complex adsorption between Cu (I) and carbon monoxide, the adsorption performance of the adsorbent for carbon monoxide is increased. There are many ways to introduce Cu (I) into traditional activated carbon-based carbon monoxide adsorbents: (1) directly use CuCl as raw material, use thermal dispersion and mix with activated carbon raw powder, and the whole process is carried out in a dry inert protective gas environment. (2) Impregnation with a solution containing Cu (II) and heating reduction in a reducing atmosphere. (3) Using a soluble salt containing Cu (II) as a precursor, Cu (II)-loaded activated carbon is prepared by thermal dispersion and then heated and reduced in a reducing atmosphere.
[0003] The preparation process of traditional activated carbon-based carbon monoxide adsorbents requires high temperature heating and activation for several hours. If Cu (II) solution is used, there will be Cu 2+ and Cl - The ions pollute the environment. At the same time, the activated carbon loaded with Cu after molding will have surface powder falling off. In fact, it is because the surface copper salt has insufficient adhesion and falls off. During the packaging, transportation and filling of the adsorbent, the surface material falls off, thereby reducing the adsorption performance. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing an activated carbon-based CO adsorbent. A new method for introducing Cu (I) is adopted, which uses a two-step thermal dispersion process, and the second step of thermal dispersion process is carried out simultaneously with the binder cross-linking reaction and Cu (II) reduction reaction, thereby preventing the Cu (II) in the traditional synthesis process from being 2+ Ions and CI - Ions pollute the environment and reduce the temperature and heating time of traditional activated carbon thermoforming.
[0005] Furthermore, after the activated carbon is formed and activated, the present invention introduces a porous cross-linked fiber: sodium carboxymethyl cellulose-sodium alginate. By spraying this porous, high-strength, low-cost coating on the surface of the formed activated carbon, it can effectively alleviate the powdering of the adsorbent surface and the shedding of the loaded copper salt without basically affecting the gas mass transfer adsorption.
[0006] A first aspect of the present invention provides a method for preparing a high-efficiency CO adsorbent.
[0007] A method for preparing a CO adsorbent of the present invention comprises the following steps:
[0008] (1) 60-80 parts by weight of activated carbon raw powder and 20-40 parts by weight of CuCl are reduced in a dry inert atmosphere to obtain activated carbon with inner pores loaded with Cu (I);
[0009] (2) 75-85 parts by weight of the Cu(I)-loaded activated carbon obtained in step (1), 5-10 parts by weight of a binder and 10-15 parts by weight of CuCl 2 ·2H 2 O mixed, then mixed with water, kneaded, and then molded;
[0010] (3) Activating the activated carbon formed body obtained in step (2) in a reducing atmosphere to obtain a CO adsorbent product.
[0011] Furthermore, the method of the present invention further comprises step (4): adding sodium alginate and sodium carboxymethyl cellulose powders to water in a certain proportion and mixing them evenly to obtain a mixed dispersion; adding CaCl 2 The solutions are mixed evenly to obtain a spraying liquid; the spraying liquid is sprayed on the surface of the CO adsorbent obtained in step (4) using a spray gun, and freeze-dried to obtain a Cu (I)-loaded carbon monoxide activated carbon-based adsorbent having a porous cross-linked fiber shell.
[0012] Furthermore, the reduction temperature in step (1) is in the range of 250-400°C, preferably 270-320°C, and the reduction time is 1-1.5 hours; the inert atmosphere used is at least one of nitrogen, argon and helium.
[0013] Furthermore, the amount of CuCl used in step (1) is not excessive, that is, lower than the dispersion threshold of the activated carbon with the corresponding iodine value, in order to make full use of the available loading surface of the activated carbon and provide some surplus for the second step of thermal dispersion. The amount of activated carbon and CuCl used depends on the specific iodine value of the activated carbon used. Generally, the amount of CuCl is 70%-80% of the corresponding dispersion threshold. The inventors of the present application have found through research that there is a corresponding relationship between the iodine value of the activated carbon raw powder and the dispersion threshold that can be loaded by one-step thermal dispersion, as shown in Table 1.
[0014] Table 1 CuCl dispersion threshold of activated carbon with different iodine values
[0015]
[0016] Furthermore, the mixing in step (2) is completed by a stirrer. The stirring speed of the mixing stirrer is generally 200-400 rpm, and the stirring time is 40-60 seconds. It should be noted that if a high speed of more than 300 rpm is used for dispersion, the friction between the activated carbon raw powder particles will generate excessive heat, which may easily oxidize part of the CuCl at high temperature. In this case, the dispersion time (i.e., the mixing and stirring process) can be divided into 2-3 sections, each with an interval of 5-10 seconds.
[0017] Furthermore, the molding in step (2) adopts conventional techniques in the art. The uniformly kneaded material is poured into a hydraulic press mold and molded at a certain temperature and pressure for a certain time. The pressure of the hydraulic molding is 7-10MPa, the temperature is 100-150°C, and it is maintained for 15-25 minutes.
[0018] Furthermore, the activation temperature in step (3) is 250-300° C., the activation time is 2-3 hours, and the reducing atmosphere is at least one of nitrogen or carbon monoxide.
[0019] Further, in step (4): the weight ratio of sodium alginate to sodium carboxymethyl cellulose is generally 2-4, preferably 2.5-3. Specifically, the weight ratio of sodium alginate to sodium carboxymethyl cellulose can be 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, and any value in the range formed by any two of these point values.
[0020] Further, after the two solutions in step (4) are mixed, the Ca 2+ A cross-linking reaction occurs in the environment, and the activated carbon surface coating process is carried out simultaneously during the cross-linking reaction process, and the mixed colloid solution after adding calcium chloride is coated on the activated carbon surface.
[0021] Furthermore, the freeze drying in step (4) is performed by conventional operations in the art. For example, freeze drying conditions are generally: freezing at -30 to -50°C for 3 to 5 hours, followed by drying under vacuum conditions for 24 hours.
[0022] According to the second aspect of the present invention, the present invention also provides a high-efficiency CO adsorbent, which is prepared by the method described above.
[0023] Furthermore, the CO adsorbent having a porous cross-linked fiber shell is a core-shell structure, wherein the length of the core layer is generally 3-10 mm, the diameter is generally 0.5-2 mm, and the thickness of the porous cross-linked fiber shell layer is generally 5-10 microns.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention first uses a non-excess amount of CuCl powder for a short-term thermal dispersion, so that Cu (I) first occupies the inside of the activated carbon pores, and then uses a thermal forming process to further achieve the purpose of complete dispersion. 2 ·2H 2 The 19wt% crystalline water contained in O reduces the amount of water added during the molding process, minimizes the sintering and oxidation of CuCl, and at the same time, the three-step thermal dispersion achieved by thermal molding is better than the traditional Cu (I) loading effect of a long thermal dispersion after or before molding. Furthermore, the last thermal dispersion achieves the dispersion of Cu (II) on the surface of activated carbon, the thermal reduction of Cu (II), and the thermal cross-linking of the binder sodium carboxymethyl cellulose, a total of three steps of reaction and one step of synthesis. In summary, compared with the traditional activated carbon-based carbon monoxide adsorbent loaded with Cu (I), the present invention achieves higher energy utilization efficiency and shorter thermal dispersion time (energy saving), and prevents the traditional synthesis process containing Cu 2+ Ions and CI - The pollution of ionic solution to the environment and the better dispersion effect of Cu(I) are shown.
[0026] 2. The present invention innovatively introduces a porous cross-linked fiber: sodium carboxymethyl cellulose-sodium alginate, which is sprayed on the surface of the formed activated carbon. It can effectively alleviate the surface powdering and shedding of the loaded copper salt of the traditional activated carbon-based carbon monoxide adsorbent loaded with Cu (I) without basically affecting the gas mass transfer adsorption, thereby increasing the stability of the adsorbent. DETAILED DESCRIPTION
[0027] The technical content and effects of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.
[0028] Example 1
[0029] Take 80 parts by weight of activated carbon powder with an iodine value of 600-700 and 20 parts by weight of CuCl powder, and heat disperse them in a tube furnace at 300°C in a nitrogen atmosphere for 1 hour. Take 80 parts by weight of activated carbon powder after heat dispersion, 10 parts by weight of sodium carboxymethyl cellulose, and 10 parts by weight of CuCl 2 ·2H 2O, put it into a mixing agitator and mix it at a speed of 300rpm for 45 seconds, add 10 parts by weight of water to the evenly mixed powder, stir it evenly, pour it into a Φ2 mold of a hydraulic press, and mold it at 8MPa and 120℃ for 20 minutes to obtain molded unactivated activated carbon. Take the molded activated carbon and put it into a tubular furnace, heat and disperse it at 270℃ in a carbon monoxide atmosphere for 3 hours to obtain a finished CO adsorbent.
[0030] Example 2
[0031] Compared with Example 1, the steps of Cu (I) loading and activated carbon forming are the same, except that the surface is coated with cross-linked porous fibers: sodium carboxymethyl cellulose, sodium alginate and water are stirred and mixed, and calcium chloride solution is added and mixed and stirred evenly. Take out the mixed solution and spray it evenly on the surface of the activated carbon product with a spray gun at room temperature, and control the spray flow rate to 0.5mL / min. The activated carbon with the surface sprayed completely is frozen at -40°C for 3 hours, and then dried under vacuum conditions for 24 hours to obtain an activated carbon-based carbon monoxide adsorbent with a final load of Cu (I) and an outer layer of sodium carboxymethyl cellulose-sodium alginate cross-linked fibers.
[0032] Example 3
[0033] Compared with Example 1, the steps of Cu(I) loading and activated carbon forming are the same, except that, in the first thermal dispersion, 70 parts by weight of activated carbon raw powder with an iodine value of 600-700 and 30 parts by weight of CuCl powder are thermally dispersed at 400°C for 1 hour.
[0034] Example 4
[0035] Compared with Example 3, the Cu(I) loading and activated carbon forming steps are the same, except that the surface is coated with cross-linked porous fibers.
[0036] Example 5
[0037] Compared with Example 1, the steps of Cu(I) loading and activated carbon forming are the same, except that the second thermal dispersion takes 70 parts by weight of the activated carbon powder obtained in the first thermal dispersion, 10 parts by weight of sodium carboxymethyl cellulose, and 20 parts by weight of CuCl 2 ·2H 2 O mixed and then reduced at 250°C for 3 hours.
[0038] Example 6
[0039] Compared with Example 5, the Cu(I) loading and activated carbon forming steps are the same, except that the surface is coated with cross-linked porous fibers.
[0040] Comparative Example 1
[0041] Take 70 parts by weight of 600-700 iodine value activated carbon powder and 30 parts by weight of CuCl powder, and heat disperse them in a tubular furnace at 300°C in a nitrogen atmosphere for 1 hour. Take 80 parts by weight of activated carbon powder after heat dispersion, mix it with 10 parts by weight of sodium carboxymethyl cellulose, put it into a mixing agitator and mix it at 300rpm for 45 seconds, add 10 parts by weight of water to the mixed powder, stir it evenly, pour it into a hydraulic press Φ2 mold, and mold it at 8MPa and 120°C for 20 minutes to obtain molded unactivated activated carbon. Take the molded activated carbon and put it into a tubular furnace, heat and disperse it at 270°C in a carbon monoxide atmosphere for 3 hours to obtain an activated carbon product without wrapped cross-linked fibers.
[0042] Comparative Example 2
[0043] Take 70 parts by weight of 600-700 iodine value activated carbon powder, 30 parts by weight of CuCl 2 ·2H 2 O powder, put it into a tubular furnace for thermal dispersion at 300℃ and nitrogen atmosphere for 1 hour. Take 80 parts by weight of the activated carbon powder after thermal dispersion, mix it with 10 parts by weight of sodium carboxymethyl cellulose, put it into a mixing agitator and mix it at 300rpm for 45 seconds, add 10 parts by weight of water to the mixed powder, stir it evenly, pour it into the Φ2 mold of the hydraulic press, and mold it at 8MPa and 120℃ for 20 minutes to obtain molded unactivated activated carbon. Take the molded activated carbon and put it into a tubular furnace, heat and disperse it at 270℃ in a carbon monoxide atmosphere for 3 hours to obtain the finished activated carbon without wrapped cross-linked fibers.
[0044] Adsorbent performance test: The evaluation methods used in Examples 1-6 and Comparative Examples 1-3 are the same. The adsorption performance was tested by a Micromatics HPVA high pressure adsorption instrument. The pretreatment conditions were 5 bar and 150°C for 4 hours under a CO atmosphere, followed by vacuuming and cooling to room temperature. The adsorption isotherm was obtained by testing, and the adsorption amount at 1 bar is listed in Table 2. The strength test was based on the national standard GB / T12496.6-1999.
[0045] The properties of the activated carbon-based CO adsorbents obtained in Examples 1-6 and Comparative Examples 1-2 are listed in Table 2.
[0046] Table 2 Properties of CO adsorbents
[0047]
[0048] As can be seen from Table 2, compared with Examples 1 and 2, Examples 3 and 4, and Examples 5 and 6, the core-shell structure affects the gas mass transfer on the adsorbent surface, which is reflected in a decrease in the adsorption amount, but at the same time improves the adsorbent strength. Compared with Example 1, Example 3 and Example 5, the introduction of excessive copper salt in the first thermal dispersion or the second thermal dispersion will cause the blockage of the activated carbon pore structure, which is reflected in a decrease in the adsorption amount, but has no obvious effect on the adsorbent strength.
[0049] Comparison between Comparative Examples 1-2 and Example 1 shows that the conventional method of using CuCl or CuCl 2 ·2H 2 As a copper source for single thermal dispersion, the copper dispersion effect is not as good as that of double thermal dispersion. The introduction of excessive copper salt once will cause the blockage of the activated carbon pore structure, which is reflected in the decrease of adsorption amount.
Claims
1. A method for preparing a CO adsorbent, comprising the following steps: (1) 60-80 parts by weight of activated carbon raw powder and 20-40 parts by weight of CuCl are reduced in a dry inert atmosphere to obtain activated carbon with inner pores loaded with Cu (I); (2) taking 75-85 parts by weight of the Cu(I)-loaded activated carbon obtained in step (1), mixing it with 5-10 parts by weight of a binder and 10-15 parts by weight of CuCl2·2H2O, and then mixing and kneading it with water, and then forming it; (3) activating the activated carbon formed body obtained in step (2) in a reducing atmosphere to obtain a CO adsorbent product; The reduction temperature in step (1) is 250-400°C and the reduction time is 1-1.5 hours; The mixing in step (2) is carried out by a stirrer, the speed of the stirrer is 200-400 rpm, and the stirring time is 40-60 seconds; The activation temperature in step (3) is 250-300°C and the activation time is 2-3 hours.
2. The preparation method according to claim 1, characterized in that: The method further comprises the step (4): adding sodium alginate and sodium carboxymethyl cellulose powders into water in a certain proportion and mixing them evenly to obtain a mixed dispersion; adding CaCl2 solution into the mixed dispersion and mixing them evenly to obtain a spraying liquid; spraying the spraying liquid onto the surface of the CO adsorbent obtained in the step (3) by using a spray gun, and freeze-drying the spraying liquid to obtain a Cu(I)-loaded carbon monoxide activated carbon-based adsorbent having a porous cross-linked fiber shell.
3. The preparation method according to claim 1 or 2, characterized in that: The reduction temperature in step (1) is 170-320°C; the inert atmosphere used is at least one of nitrogen, argon and helium.
4. The preparation method according to claim 1, characterized in that: The rotation speed of the stirrer is higher than 300 rpm, and the stirring process is divided into 2-3 sections, with an interval of 5-10 seconds between each section.
5. The preparation method according to claim 1 or 2, characterized in that: The molding pressure in step (2) is 7-10 MPa, the temperature is 100-150°C, and it is maintained for 15-25 minutes.
6. The preparation method according to claim 1 or 2, characterized in that: The gas atmosphere used in step (3) is at least one of nitrogen and carbon monoxide.
7. The preparation method according to claim 2, characterized in that: In step (4): the weight ratio of sodium alginate to sodium carboxymethyl cellulose is 2-4.
8. The preparation method according to claim 1, characterized in that: The freeze-drying conditions of step (4) are: freezing at -30 to -50°C for 3 to 5 hours, followed by drying under vacuum conditions for 24 hours.
9. A high-efficiency CO adsorbent obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Adsorbent for recovering CO from industrial exhaust gas as well as preparation method and application of adsorbent
CN104492375A
Preparation method of monomolecular-layer CuCl / activated carbon adsorbent for CO adsorption separation
CN108704609A